Gabapentin Enacarbil Extended‐Release for Alcohol Use Disorder: A Randomized, Double‐Blind, Placebo‐Controlled, Multisite Trial Assessing Efficacy and Safety. (9th December 2018) - Falk, Daniel E.; Ryan, Megan L.; Fertig, Joanne B.; Devine, Eric G.; Cruz, Ricardo; Brown, E. Sherwood; Burns, Heather; Salloum, Ihsan M.; Newport, D. Jeffrey; Mendelson, John; Galloway, Gantt; Kampman, Kyle; et al.
Abstract : Background: Several single‐site alcohol treatment clinical trials have demonstrated efficacy for immediate‐release (IR) gabapentin in reducing drinking outcomes among individuals with alcohol dependence. The purpose of this study was to conduct a large, multisite clinical trial of gabapentin enacarbil extended‐release (GE‐XR) (HORIZANT ® ), a gabapentin prodrug formulation, to determine its safety and efficacy in treating alcohol use disorder (AUD). Methods: Men and women ( n  =   346) who met DSM‐5 criteria for at least moderate AUD were recruited across 10 U.S. clinical sites. Participants received double‐blind GE‐XR (600 mg twice a day) or placebo and a computerized behavioral intervention (Take Control) for 6 months. Efficacy analyses were prespecified for the last 4 weeks of the treatment period. Results: The GE‐XR and placebo groups did not differ significantly on the primary outcome measure, percentage of subjects with no heavy drinking days (28.3 vs. 21.5, respectively, p  =   0.157). Similarly, no clinical benefit was found for other drinking measures (percent subjects abstinent, percent days abstinent, percent heavy drinking days, drinks per week, drinks per drinking day), alcohol craving, alcohol‐related consequences, sleep problems, smoking, and depression/anxiety symptoms. Common side‐effects were fatigue, dizziness, and somnolence. A population pharmacokinetics analysis revealed that patients had lower gabapentin exposure levels compared with those in other studies using a similar dose but for other indications. Conclusions: Overall, GE‐XR at 600 mg twice a day did not reduce alcohol consumption or craving in individuals with AUD. It is possible that, unlike the IR formulation of gabapentin, which showed efficacy in smaller Phase 2 trials at a higher dose, GE‐XR is not effective in treating AUD, at least not at doses approved by the U.S. Food and Drug Administration for treating other medical conditions. Abstract : Gabapentin enacarbil extended‐release (GE‐XR) (HORIZANT) at 600 mg twice a day did not reduce alcohol consumption or craving in individuals with alcohol use disorder, including the primary outcome – the percentage of subjects with no heavy drinking days (PSNHDD). There was no significant difference between GE‐XR and placebo on PSNHDD across trial months and across the entire maintenance period (Weeks 2 to 25) (all ps > 0.05).